STRATEGI KOMUNIKASI PEMASARAN EKOWISATA PADA DESTINASI WISATA DOLPHIN HUNTING LOVINA - Karta, Ni Luh Putu Agustini; Suarthana, I Ketut Putra (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 8 Nomor 1 Tahun 2014)
The purpose of this research is to find the right marketing communications strategy for Ecotourism’s Destinations, (Dolphin Hunting Lovina), to be sustainable. Design methodology used is a marketing communication approach by adopting the concept of basic elements of the theory of marketing communication, the shift towards integrated marketing approach marketing communications, and public organizational challenges in creating brand awareness. Qualitative research and in-depth interviews carried out to some competent resource. The findings generated that image creation and brand awareness of Dolphin Hunting Lovina is determined by the  organization’s marketing communications and internal audiences
Keywords: marketing, communications, images, destinations, sustainable